Efektifitas Mindfulness Islami terhadap Intensitas Mual pada Pasien Tuberkulosis - Sajodin Sajodin; Rodiah Surya; Inggriane Puspita Dewi (Faletehan Health Journal, 2024)
Side effects of tuberculosis (TB) treatment with anti-tuberculosis drugs (ATDs) often include nausea. To address this symptom, an Islamic mindfulness approach is needed. Therefore, this study aimed to assess the effectiveness of Islamic mindfulness in reducing nausea intensity among TB patients undergoing ATD therapy. The research followed a quasi-experimental design with a pre-post test control group design. The study included TB patients experiencing nausea symptoms during ATD therapy. The sample of 38 participants was selected through consecutive sampling, which 19 individuals assigned to the intervention group receiving an Islamic mindfulness program consisting of meditation exercises and Islamic reflection, while the remaining 19 individuals formed the control group receiving standard care. Nausea intensity was measured using the Index Nausea Vomiting and Retching (INVR) scale before and after the intervention. The results demonstrated that the intervention group experienced a significantly greater reduction in nausea intensity compared to the control group (p<0.0001), with a Cohen's-d effect size of 2.04. Over 98.0% of patients in the intervention group showed a reduction in nausea intensity surpassing the control group's average. In conclusion, this study indicated that Islamic mindfulness is effective in alleviating nausea intensity among TB patients undergoing ATD therapy.